2007
DOI: 10.1091/mbc.e07-05-0428
|View full text |Cite
|
Sign up to set email alerts
|

Type Iγ PIP Kinase Is a Novel Uropod Component that Regulates Rear Retraction during Neutrophil Chemotaxis

Abstract: Cell polarization is necessary for directed migration and leukocyte recruitment to inflamed tissues. Recent progress has been made in defining the molecular mechanisms that regulate chemoattractant-induced cell polarity during chemotaxis, including the contribution of phosphoinositide 3-kinase (PI3K)-dependent phosphatidylinositol (3,4,5)-trisphosphate [PtdIns(3,4,5)P 3 ] synthesis at the leading edge. However, less is known about the molecular composition of the cell rear and how the uropod functions during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(85 citation statements)
references
References 51 publications
2
81
0
Order By: Relevance
“…The ability of PIP5Ks to induce focal-adhesion dissolution suggests that PtdIns(4,5)P 2 synthesis might induce the loss of cell-matrix interactions at the rear of migrating cells. Indeed, in neutrophils, both PIP5K and PIP5K are located in the uropod, a structure formed at the rear of a migrating neutrophil (Lacalle et al, 2007;Lokuta et al, 2007). PIP5K is targeted to the uropod through its C-terminal tail and binds to the uropod-based complex of ERM and EBP50 (Fig.…”
Section: Cellular Functions Of Pip5ksmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of PIP5Ks to induce focal-adhesion dissolution suggests that PtdIns(4,5)P 2 synthesis might induce the loss of cell-matrix interactions at the rear of migrating cells. Indeed, in neutrophils, both PIP5K and PIP5K are located in the uropod, a structure formed at the rear of a migrating neutrophil (Lacalle et al, 2007;Lokuta et al, 2007). PIP5K is targeted to the uropod through its C-terminal tail and binds to the uropod-based complex of ERM and EBP50 (Fig.…”
Section: Cellular Functions Of Pip5ksmentioning
confidence: 99%
“…Although ERM proteins can be activated by interacting with PtdIns(4,5)P 2 , the kinase activity of PIP5K is not essential for uropod retraction (Lacalle et al, 2007). By contrast, PIP5K localisation to the uropod and its kinase activity were found to be important for neutrophil chemotaxis (Lokuta et al, 2007). Therefore, it is possible that both PIP5K and PIP5K have distinct functions in uropod retraction.…”
Section: Cellular Functions Of Pip5ksmentioning
confidence: 99%
“…mAbp1 was PCR amplified from GFP-mAbp1 and GFP-mAbp1(W415K) (Cortesio et al, 2010) using a forward primer containing an EcoRI site, 59-GTC ACG GAA TTC GAT GGC GGT GAA CCT GAG CCG GAA C-39 and BamHIcontaining reverse primer, 59-CGA TCG CGG ATC CTC ACT CTA TGA GCT CCA CGT AGT TGG CAG G-39. PCR-amplified mAbp1 and mAbp1(W415K) was cloned into the EcoRI and BamHI sites of pmCherry-C1 (Lokuta et al, 2007). mCherry-C1-mAbp1 and mCherry-C1-Abp(W415K) were subcloned into pMXIres-GFP vector (Clive Svendsen, University of Wisconsin, Madison, WI) with the Ires-GFP portion excised.…”
Section: Dna and Sirna Constructsmentioning
confidence: 99%
“…We suggest that activation of PIP5K and increased local synthesis of PtdIns(4,5)P 2 at the trailing edge of a migrating cell regulates vinculin interactions, to decrease focal adhesion stability. Interestingly, a recent study has demonstrated that PIP5K is localised to the uropod and that PtdIns(4,5)P 2 synthesis is required for uropod retraction during neutrophil migration (Lokuta et al, 2007).…”
Section: E61lmentioning
confidence: 99%